PERANCANGAN PROMOSI ENDORSEMENT BERBAYAR PADA PERUSAHAAN PIETISIERE - Ebelliana, Meike; Mustikarini, Carolina Novi (PERFORMA, 2017)
The popularity of the internet as a marketing media is an opportunity to boost marketing through online media. One of the online marketing strategies is paid endorsement. The main topic of this research is the use of Instagram as the platform for Pietisiere’s paid endorsement. The purpose of this research is to design the paid endorsement strategy for Pietisiere. This research is a descriptive qualitative research. Four informants are chosen as samples using purposive sampling technique. This research uses participatory observation and semi-structured interview as data collection methods. The result of this research indicates that the paid endorsement strategy requires several phases, which are social media segmentation analysis, the selection of appropriate endorsers, endorser criteria analysis, time period analysis, paid endorsement agreement analysis, and the optimization of Instagram features